Clinical characteristics and genetics of ten Chinese children with PRRT2-associated neurological diseases - Liu, Meiyan; Sun, Xiaoang; Lin, Longlong; Luo, Xiaona; Wang, Simei; Wang, Chunmei; Zhang, Yuanfeng; Xu, Quanmei; Xu, Wuhen; Wu, Shengnan; Lan, Xiaoping; Chen, Yucai (Frontiers in Pediatrics, 2022)
Background: Proline-rich transmembrane protein 2 (PRRT2) plays an important role in the central nervous system and mutations in the gene are implicated in a variety of neurological disorders. This study aimed to summarize the clinical characteristics and gene expression analysis of neurological diseases related to the PRRT2 gene and explore the clinical characteristics, therapeutic effects, and possible pathogenic mechanisms of related diseases. Methods: We enrolled 10 children with PRRT2 mutation-related neurological diseases who visited the Children's Hospital affiliated with the Shanghai Jiaotong University School of Medicine/Shanghai Children's Hospital between May 2017 and February 2022. Video electroencephalography (VEEG), cranial imaging, treatment regimens, gene results, and gene expression were analyzed. Genetic testing involved targeted sequencing or whole-exome genome sequencing (WES). We further analyzed the expression and mutation conservation of PRRT2 and synaptosome-associated protein 25 (SNAP25) in blood samples using quantitative polymerase chain reaction (qPCR) and predicted the protein structure. Summary analysis of the reported gene maps and domains was also performed. Results: Ten children with PRRT2 gene mutations were analyzed, and 4 mutations were identified, consisting of 2 new (c.518A>C, p.Glu173 Ala; c.879+112G>A, p.?) and two known (c. 649 dup, p. Arg217Profs * 8; c. 649 del, p. Arg217Glufs * 12) mutations. Among these mutations, one was de novo（P6）, and three could not be determined because one parent refused genetic testing. The clinical phenotypes were abnormal paroxysmal disease, benign familial infantile epilepsy (BFIE), epilepsy, infantile spasms, and intellectual disability. The qPCR results showed that PRRT2 gene expression levels were significantly lower in children and parent carriers than the control group. The SNAP25 gene expression level of affected children was significantly lower (P ≤ 0.001) than that of the control group. Conclusion: Mutation of PRRT2 led to a significant decrease in its protein expression level and that of SNAP25, suggesting that the mutant protein may lead to the loss of its function and that of related proteins. This mutation site is highly conserved in most species, and there was no significant correlation between specific PRRT2 genotypes and clinical phenotypes. Asymptomatic carriers also have decreased gene expression levels, suggesting that more factors are involved.